Real‐time imaging of sodium glucose transporter (SGLT1) trafficking and activity in single cells. Issue 3 (13th February 2017) - Ghezzi, Chiara; Calmettes, Guillaume; Morand, Pauline; Ribalet, Bernard; John, Scott
Abstract: The processes controlling targeting of glucose transporters to apical and basolateral membranes of polarized cells are complex and not‐well understood. We have engineered SGLT1 and GLUT4 constructs linked to fluorescent proteins to highlight the differences in transporter expression and trafficking, in real time, in different cell types. Activity was assessed in parallel using a FRET glucose sensor. In COS cells and HEK cells, SGLT1 was distributed between the plasma membrane and intracellular compartments, but there was little expression in CHO cells. Trafficking was investigated using the lysosome inhibitors NH4 Cl (10 mmol/L) and chloroquine (150 μ mol/L) and the proteasome inhibitors MG‐262 (1 μ mol/L) and lactacystin (5 μ mol/L). Lysosome inhibitors caused SGLT1 accumulation into intracellular bodies, whereas proteasome inhibitors induced SGLT1 accumulation in the plasma membrane, even in CHO cells. Our data suggest that a fraction of SGLT1 is rapidly degraded by lysosomes and never reached the plasma membrane; another fraction reaches the membrane and is subsequently degraded by lysosomes following internalization. The latter process is regulated by the ubiquitin/proteasome pathway, acting at a late stage of the lysosomal pathway. Using the cholesterol inhibitor M β CD (3 mmol/L), a dominant negative dynamin (K44A) and caveolin, we showed that SGLT1 internalization is lipid raft‐mediated, but caveolin‐independent. In contrast, GLUT4 internalization is dynamin‐dependent, but cholesterol‐independent. The physiological relevance of these data is discussed in terms of differential membrane compartmentalization of the transporters and expression under stress conditions. Abstract : The Na/Glucose transporter (SGLT1) has been extensively studied in epithelium, but little is known about its role in other tissues, even though recent reports have shown up regulation of this transporter in cancer cells and cardiac tissues under stress. Moreover, even in epithelial cells, targeting of SGLT1 to the apical membrane, which is essential for transepithelial glucose transport, remains poorly understood. We have engineered fluorescent SGLT1 constructs to investigate, in live cells and in real‐time, the trafficking of SGLT1 in three cell lines: CHO, COS, and HEK. A firm understanding of this process in such simple cell systems should allow us to characterize the trafficking and role of this transporter in complex systems, such as tumors and cardiac tissues.